Biodegradation of an injectable treated dentin matrix hydrogel as a novel pulp capping agent for dentin regeneration - Ahmed A. Holiel; Hossam M. Mustafa; Eman M. Sedek (BMC, 2023)
Abstract Background A novel injectable mixture termed treated dentin matrix hydrogel (TDMH) has been introduced for restoring dentin defect in DPC. However, no study evaluated its physiological biodegradation. Therefore, the present study aimed to assess scaffold homogeneity, mechanical properties and biodegradability in vitro and in vivo and the regenerated dentin induced by TDMH as a novel pulp capping agent in human permanent teeth. Methods Three TDMH discs were weighted, and dry/wet ratios were calculated in four slices from each disc to evaluate homogeneity. Hydrogel discs were also analyzed in triplicate to measure the compressive strength using a universal testing machine. The in vitro degradation behavior of hydrogel in PBS at 37 °C for 2 months was also investigated by monitoring the percent weight change. Moreover, 20 intact fully erupted premolars were included for assessment of TDMH in vivo biodegradation when used as a novel injectable pulp capping agent. The capped teeth were divided into four equal groups according to extraction interval after 2-, 8-, 12- and 16-weeks, stained with hematoxylin-eosin for histological and histomorphometric evaluation. Statistical analysis was performed using F test (ANOVA) and post hoc test (p = 0.05). Results No statistical differences among hydrogel slices were detected with (p = 0.192) according to homogeneity. TDMH compression modulus was (30.45 ± 1.11 kPa). Hydrogel retained its shape well up to 4 weeks and after 8 weeks completely degraded. Histological analysis after 16 weeks showed a significant reduction in TDMH area and a simultaneous significant increase in the new dentin area. The mean values of TDMH were 58.8% ± 5.9 and 9.8% ± 3.3 at 2 and 16 weeks, while the new dentin occupied 9.5% ± 2.8 at 2 weeks and 82.9% ± 3.8 at 16 weeks. Conclusions TDMH was homogenous and exhibited significant stability and almost completely recovered after excessive compression. TDMH generally maintained their bulk geometry throughout 7 weeks. The in vivo response to TDMH was characterized by extensive degradation of the hydrogel and dentin matrix particles and abundant formation of new dentin. The degradation rate of TDMH matched the rate of new dentin formation. Trial registration: PACTR201901866476410: 30/1/2019.